Kepemimpinan Spiritual dan Kebertahanan Pondok Pesantren di Era Masyarakat 5.0 di Pondok Pesantren Al-Asy'ary, Purwakarta - Shalha Nurul Afifah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the role of spiritual leadership of the kiai in strengthening the organizational resilience of Al-Asy’ary Islamic Boarding School in the era of Society 5.0. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the kiai, teachers, and students, as well as observation and supporting documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the kiai’s spiritual leadership is a key determinant of pesantren resilience through the integration of transcendental, ethical-humanistic, and adaptive-progressive dimensions. The kiai successfully guides the selective and meaningful use of digital technology by positioning it as a means of service (khadam), rather than an end in itself. Leadership practices based on role modeling, moral values, and spiritual reinforcement foster students’ moral autonomy and create a stable organizational climate amid digital disruption. This study concludes that the resilience of traditional pesantren in the Society 5.0 era lies in the strength of spiritual values sustained through adaptive and continuous spiritual leadership.